The Synergistic Effect of Academic Supervision and Principal Motivation on Teacher Performance: Evidence from Public High Schools in Indonesia - Deti Harlena; Alhadi Yan Putra; Nurlina Nurlina (Journal of Social Work and Science Education, 2026)
Teacher performance gaps remain a persistent challenge in improving educational quality, influenced by the effectiveness of academic supervision and principals’ motivational leadership. This study examines the extent to which these two factors contribute to the performance of public senior high school teachers in Banyuasin Regency. Employing a quantitative approach with a correlational design, the research involved 126 teachers selected through random sampling. The measurement instruments demonstrated adequate construct validity (AVE > 0.50) and reliability (Cronbach’s Alpha > 0.70). Multiple linear regression analysis revealed that academic supervision (β = 0.261; p = 0.003) and principal motivation (β = 0.373; p < 0.001) exert significant positive effects on teacher performance, both individually and jointly (F = 11.222; p < 0.001), yielding an R² value of 0.154. These findings underscore the relevance of Self-Determination Theory in explaining how leadership support fulfills teachers’ psychological needs. Practically, the results highlight the importance of strengthening coaching-based supervision and motivational strategies to foster a more supportive professional environment and promote continuous performance improvement.